RECOVERY OF PHYSICAL CONDITION OF THE HUMAN OPERATOR, WORKING AT HYPODYNAMY - A. E. Karpinskiy; P. M. Polyakov; A. Yu. Ableev (Научный вестник МГТУ ГА)
The article touched upon the problem of providing health to human operator in carrying out the works-rest, characterized by a special responsibility and neuro-emotional high-voltage by means of the use of physical exercise. On the example of aviation event the importance of restoring the physical conditions transition from the monotonous stage to high-level, short-termism, crucial stage is shown (for example, the transition from cruise flight mode, taking place in the automatic mode to landing).